Optimizing Methanol Production Yield through Carbon Dioxide Hydrogenation Process with Continuous Stirred Tank Reactor and Transition from Partial to Total Condenser in Distillation - Verisna, Chindaga Widya; Lissa'adah, Munna; Nursatitah, Nursatitah; Aulia, Zulfa (UPT Laboratorium Terpadu, Universitas Diponegoro, 2025)
Methanol is a chemical product that is widely applied in the chemical industry. The methanol production process from carbon dioxide and hydrogen uses a hydrogenation process with a continuous stirred tank reactor (CSTR) under controlled thermodynamic and kinetic conditions. The process was modified by replacing the Gibbs reactor with a Continuous Stirred Tank Reactor (CSTR), adding temperature and pressure regulation, and a compressor. This study aims to increase the product yield obtained from the modification results and mass efficiency. Based on the experimental results, it can be concluded that the modified design is quite effective compared to before modification, because it increases the methanol product yield from 44.54% to 99.78%. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).